Tomato Plant Production (Lycopersicum esculentum, Mill) Due to Main Branch Pruning and GDM Liquid Organic Fertilizer (POC) Concentration - Ulya J. Riwu Kaho; Joritha Naisanu; Henny A. Raga (Jurnal Penelitian Pendidikan IPA, 2025)
Tomatoes (Lycopersicum esculentum, Mill) are classified as fruit vegetables that contain a lot of water, store a lot of seeds, contain vitamins A and C, and a little vitamin B. To ensure the availability of tomato production, improvements are needed, including pruning and liquid organic fertilizers. The study aimed to determine the effect of pruning and GDM POC on the growth and production of tomato plants. The design used was a factorial RAK pattern consisting of factor I: pruning the main shoot; P0: No pruning (control) P1: pruning the main shoot; Factor II: GDM POC; G0: Control (GDM Fertilizer); G1: concentration of 2 ml/liter of water/plot; G2: Concentration of 4 ml/liter of water/plot; G3: Concentration of 6 ml/liter of water/plot. The study's results showed that pruning the main branches and giving GDM POC concentration to tomatoes significantly affected the yield of tomato plants. The P1G3 treatment produced the best growth and yield of tomato plants. The interaction between pruning of the main branches and giving of 6 ml plot-1 concentration resulted in an average plant height of 98 cm, number of leaves 131 strands, flowering age 32 HST, number of fruits 2 plants-1, and fruit weight 21.83 g. The conclusion is that pruning and GDM POC influence the growth and production of tomato plants.